A parametric analysis of the earth air heat exchangers’ thermal efficiency and their effect on surrounding soil over time - Boutera, Yousra; Boultif, Nora; Moummi, Noureddine; Beldjani, Charafeddine; Kethiri, Mohamed Aymen; Momen SM, Saleh; Müslüm, Arıcı (Journal of Applied Engineering Science and Technology, 2025)
Earth Air Heat Exchanger (EAHE) system is widely regarded as an efficient and sustainable solution, minimizing the consumption of energy and enhancing indoor thermal comfort. This study seeks to conduct a detailed analysis of the parameters that affect the performance of EAHE systems, including the surrounding soil, climatic conditions, and time variations. A semi analytical numerical model was used and verified with existing literature data. Key parameters such as air velocity, operational periods, and soil thermal conductivity were investigated for their effect on the performance of the EAHE and the surrounding soil. The findings revealed that the model provided predictions that strongly agreed with experimental results, with only a 2.3% error margin. The study found that EAHE performance is predominantly influenced by higher soil conductivity and lower airflow velocity. In contrast, the duration of operation had minimal effect on the outlet air temperature, which increased by just 1 °C over 48 h compared to the 1st h. Lastly, the cooling of the surrounding atmosphere was identified as a key factor in enhancing the exchanger's efficiency, as it helps cool the soil after extended operation, thus restoring its cooling ability. Highlights EAHE outlet temp rose only 1 °C after 48 h continuous operation. Higher soil conductivity enhances heat transfer and cooling. Increased air velocity reduces heat exchange and cooling effect. Soil heats up over time, reducing EAHE performance without rest. Model was validated with just 2.3% error vs. experimental data.